Clinical Findings of Pelvic Inflammatory Diseases among women in Reproductive Age - Laizu, Ismat Ara; Banu, Laila Anjuman; Fayez, Fowzia Abul (Journal of National Institute of Neurosciences Bangladesh, 2021)
Background: Pelvic Inflammatory disease is a very common gynaecological condition among the women in reproductive age group. Objectives: The purpose of the present study was to find out the clinical findings of Pelvic inflammatory diseases among the women during reproductive age group. Methodology: This cross-sectional study was carried out in the Department of Obstetrics and Gynaecology at Mymensingh Medical College Hospital, Mymensingh, Bangladesh from January 2008 to June 2009 for a period of one (01) and a half year. Women who were presented with pelvic inflammatory disease (PID) attended at the OPD of gynecology Department at Mymensingh Medical College Hospital, Mymensingh, Bangladesh were selected as study population. Detailed clinical history of each patient was taken and thorough physical examination was performed. Result: A total number of 300 cases were recruited. The mean age with SD was 30.3±9.57 years. Majority of the patients had tenderness in the lower abdomen which was 96(64.0%) cases. However, 152(50.7%) patients had vaginal discharge and 34(11.3%) patients had uterovaginal proplapse. However, cervical tear was present in 96(32.0%) cases and chronic cervicitis was present in 138(46.0%) cases. Conclusion: In conclusion most common clinical feature is lower abdominal tenderness followed by vaginal discharge. Journal of National Institute of Neurosciences Bangladesh, January 2021, Vol. 7, No. 1, pp. 52-55